2009 IEEE International Conference on Robotics and Biomimetics (ROBIO) 2009
DOI: 10.1109/robio.2009.5420418
|View full text |Cite
|
Sign up to set email alerts
|

An analytical approach for better swimming efficiency of slender fish robots based on Lighthill's model

Abstract: In this initial work, we discuss the application of Lighthill's small-amplitude elongated body theory (EBT) in improving the swimming efficiency. The prototype considered in the study is a slender fish model capable of performing various motion patterns. The mechanical design of the prototype, derivation of equations and the results are first discussed. We apply a body motion function with linear envelop to control the swimming of fish robot. We also study the influence of different combinations of amplitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…The distance between these two points is found to be 0.482765046 units which is also the shortest distance (normal between the two planes). In the Lighthill quadratic wave equation, the amplitude constants c 1 and c 2 have been assumed to have a value [27] with little information on their choice. Our present research looks into the real kinematics of carangiform tuna fish in [17] as well as in the kinematic formulation of the Robotuna [17].…”
Section: Resultsmentioning
confidence: 99%
“…The distance between these two points is found to be 0.482765046 units which is also the shortest distance (normal between the two planes). In the Lighthill quadratic wave equation, the amplitude constants c 1 and c 2 have been assumed to have a value [27] with little information on their choice. Our present research looks into the real kinematics of carangiform tuna fish in [17] as well as in the kinematic formulation of the Robotuna [17].…”
Section: Resultsmentioning
confidence: 99%
“…The velocities have been measured at different tailbeat frequencies ranging from 0.05 hz to 0.8 Hz. Compared to the other simulated forward velocity [10] (u = 0.12 m/s at f = 0.1Hz) and (u = 0.115m/s at f = 0.64 Hz), present result seems evenly realistic and even reaches a maximum of 1.1 BL/s (body length per second), i.e., u max = 0.138 m/s at f = 0.33 Hz, which may demonstrate the oscillatory caudal fin contributing more to thrust generation. The simulation results verify the real time kinematic studies reported by Dewar [8] in accordance with Lighthill theory.…”
Section: A Oscillatory Frequency (Tail Beat Frequency Tbf) Based Conmentioning
confidence: 97%
“…The literature [10] reports the increase of swimming speed with the oscillating frequency f, and it approaches a constant value i.e. a steady speed is achieved.…”
Section: A Oscillatory Frequency (Tail Beat Frequency Tbf) Based Conmentioning
confidence: 99%
“…In the kinematic experiments [14,19], the emphasis was on the derivation of forward speed ranges and configuration (work) space of the vehicle during the undulatory motion of the posterior part. An efficiency term/performance factor associated to the overall locomotion mechanism was also proposed [16,19]. Expected and suitable values of hydrodynamic parameters like drag coefficient, Reynolds number were assumed to obtain the net forces and, therefore, the forward velocity of the body.…”
Section: Cfd Modeling Of Lighthill Undulatory Motionmentioning
confidence: 99%
“…In 1960s a series of pioneering work on swimming mechanism by Sir Lighthill [5] emphasized on the adaptability of morphological traits as the major reason behind the hydrodynamic efficiency of fish slender body swimming. Therefore, it is shown and believed that Lighthill (LH) slender body swimming mathematical model [5] can play a vital role to envisage the undulatory wave propulsion mechanism of a biomimetic robotic fish [11,15,16]. Fishes propel themselves by exerting force against fluid (aqueous) and balancing energy with the surrounding.…”
Section: Introductionmentioning
confidence: 99%